2016
DOI: 10.1371/journal.pmed.1001974
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance in India: Drivers and Opportunities for Action

Abstract: Ramanan Laxminarayan and Ranjit Roy Chaudhury examine the factors encouraging the emergence of antibiotic resistance in India, the implications nationally and internationally, and what might be done to help.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
334
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(345 citation statements)
references
References 22 publications
(28 reference statements)
8
334
0
3
Order By: Relevance
“…India is one of the highest consumers of antibiotic drugs in the world. 5 Studies from different parts of India have consistently documented an ominously rising level of resistance to all the common antibiotics. 5 Over the last decade, published data have revealed doubling or even tripling of the rate of antibiotic resistance for almost all groups of clinically important pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…India is one of the highest consumers of antibiotic drugs in the world. 5 Studies from different parts of India have consistently documented an ominously rising level of resistance to all the common antibiotics. 5 Over the last decade, published data have revealed doubling or even tripling of the rate of antibiotic resistance for almost all groups of clinically important pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Organization for Economic Co-operation and Development (OECD) report indicated that the costs of withdrawing antimicrobial growth promoters in India would be roughly US$1.1 billion (Laxminarayan and Chaudhury, 2016). In 2010, China was the largest antimicrobial consumer for livestock, and we estimate that its livestock industry will use up to 30% of the global antimicrobial production by 2030.…”
Section: Therapeutic Cost Analysismentioning
confidence: 94%
“…16 Moreover, per capita consumption of last resort antibiotics such as carbapenem increased to over 10 million standard units by 2010. 17 In addition to the rampant use of powerful antibiotics, India is faced with perennial public health concerns like inadequate access to toilets and poorly implemented infection-control measures in hospitals. For instance, results of a pointprevalence study conducted in a large 1800-bed tertiary care hospital in India showed an overall hospital-acquired infection (HAI) prevalence of 7 percent.…”
Section: The Growing Severity Of Problem In Indiamentioning
confidence: 99%